Penyuluhan Penganggaran untuk Wirausaha pada Anggota Kelompok Mujur Fish Farm di Dusun Brengosan, Sleman, Yogyakarta - Bhenu Artha; Antonius Satria Hadi; Bahri Bahri; Ardhi Khairi; Niken Permata Sari (Universitas Negeri Makassar, 2022)
This community service activity to give counseling to fish farmer groups in Dusun Brengosan, Donoharjo Village, Ngaglik, Sleman, Yogyakarta Special Region which aims to provide additional understanding and knowledge to the fish farmer group